Behavioral Consequences and Cortical Reorganization in Homonymous Hemianopia - Chokron, Sylvie; Perez, Céline; Peyrin, Carole (Frontiers in Systems Neuroscience, 2016)
Abstract The most common visual defect to follow a lesion of the retrochiasmal pathways is homonymous hemianopia (HH), whereby, in each eye, patients are blind to the contralesional visual field. From a behavioral perspective, in addition to exhibiting a severe deficit in their contralesional visual field, hemianopic patients can also present implicit residual capacities, now usually referred to collectively as blindsight. It was recently demonstrated that HH patients can also suffer from a subtle deficit in their ipsilesional visual field, called sightblindness (the reverse case of blindsight). Furthermore, the nature of the visual deficit in the contralesional and ipsilesional visual fields, as well as the pattern of functional reorganization in the occipital lobe of HH patients after stroke, all appear to depend on the lesion side. In addition to their contralesional and ipsilesional visual deficits, and to their residual capacities, HH patients can also experience visual hallucinations in their blind field, the physiopathological mechanisms of which remain poorly understood. Herein we review blindsight in terms of its better-known aspects as well as its less-studied clinical signs such as sightblindness, hemispheric specialization and visual hallucinations. We also discuss the implications of recent experimental findings for rehabilitation of visual field defects in hemianopic patients.